EFFECT OF STIMULATORS AND SILICON COMPLEX FERTILIZERS ON THE NUMBER OF SOYBEAN VARIETIES - Kamalova Nuriya Shamilevna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This article presents data on the effect of separate and combined application of stimulants and silicon complex fertilizers on soybean varieties on their number of branches. It was found that stimulants and silicon complex fertilizers had a good effect on the number of number of branches, and in both varieties, the number of branches was higher when using Maltamin from the stimulants, when comparing stimulants with silicon complex fertilizer, and when using stimulants with silicon complex, silicon complex fertilizer + Maltamin was taken highest number of branches.